ANALISIS PENGARUH KONFLIK INTERNAL, KECERDASAN EMOSIONAL DAN TIPE KEPRIBADIAN TERHADAP KINERJA PEGAWAI NEGERI SIPIL (PNS) DI LINGKUNGAN PEMERINTAHAN KABUPATEN MINAHASA TENGGARA. - Rosalia Viva Novianni Dumondor; Willem J. F. A. Tumbuan; Rita N. Taroreh (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Human resources are a very vital asset for the progress and development of the organization due to the changes that occur. Human resources are required to continuously be able to develop their abilities proactively. To have good human resources, an organization must have good human resource management in managing human resources in the organization.This study aims to analyze the effect of Internal Conflict, Emotional Intelligence and Personality Type on the Performance of Civil Servants in Southeast Minahasa Regency. The population in this research was involve the Civil Servants at Southeast Minahasa Regency which amounted to 781. Sampling in this research using the slovin-cluster random sampling of 100 respondents. The research technique uses multiple linear regression. The results of simultaneous hypothesis testing show that the variables of Internal Conflict, Emotional Intelligence, and Personality Type together have a significant effect on employee performance. The partial test results show that the Internal Conflict variable has a negative and significant effect on the Performance variable, the Emotional Intelligence variable has a negative and significant effect on the Performance variable, the Personality Type variable has a positive and insignificant effect on the Performance variable.